R&D and the agglomeration of industries - Kranich, Jan (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2008)
This paper discusses a model of the New Economic Geography, in which the seminal core-periphery model of Krugman (1991) is extended by endogenous research activities. Beyond the common ’anonymous’ consideration of R&D expenditures within fixed costs, this model introduces vertical product differentiation, which requires services provided by an additional R&D sector. In the context of international factor mobility, the destabilizing effects of a mobile scientific workforce are analyzed. In combination with a welfare analysis and a consideration of R&D promoting policy instruments and their spatial implications, this paper makes a contribution to the so-called brain drain debate.
Keywords: Ökonomie; Geographie; 330 Wirtschaft